The Star Gate Archives : Reports of the United States Government Sponsored Psi Program, 1972–1995. Volume 3: Psychokinesis compiled and edited by Edwin C. May and Sonali Bhatt Marwaha - Mörck, Nemo C. (Journal of Scientific Exploration, 2020)
The remote viewing research conducted at Stanford Research Institute (SRI) and later at Science Applications International Corporation (SAIC) was covered in The Star Gate Archives Volumes 1 and 2, both reviewed in this journal (see Mörck, 2018, 2019). Less well-known is the fact that much psychokinesis (PK) research was also carried out. This research “ . . . was never intended to be an academic exercise typical of most laboratories. Rather, the only interest was to determine the degree to which PK might be used as part of a defensive or even offensive weapon system” (p. 12). This sounds dramatic. To U.S. intelligence agencies, a proper threat assessment was deemed necessary due to research conducted in the Soviet Union. The research in America, at SRI, was initially directed by Harold Puthoff from 1972 on, and later, for about ten years, by one of the volume’s editors, Edwin May. In addition to research reports and reviews, Volume 3, like its predecessor volumes, includes nine appendixes, a list of abbreviations, an extensive glossary, an author index, and a subject index. The papers are arranged chronologically, but it is not necessarily a good idea to read them in that order.